Upaya Pembentukan Karakter Disiplin dan Tanggung Jawab Siswa - Riski Renaldi; Rahmi Wiza (An-Nuha, 2022)
This research discusses the role of Islamic Religious Education (PAI) teachers in the formation of students' character. The characters studied are discipline and responsibility. This research is motivated by our nation's declining discipline in terms of punctuality, and also the problem of student disorder in learning which results in failure to achieve good grades. In addition, the current sense of human responsibility towards the environment and nature is not getting better, which is the background of this research. This study aims to examine: 1) The Contribution of Islamic Education Teachers inthe Efforts to Form Disciplined Characters and Student Responsibilities at SMAN 4 Sungai Penuh, 2) Inhibiting and Supporting Factors in Efforts to Form Disciplined Characters and Student Responsibilities at SMAN 4 Sungai Penuh. The method used by researchers in this study is qualitative with a descriptive approach. This research was conducted at SMAN 4 Sungai Penuh. Data collection techniques used are observation, documentation and interviews. The results showed that the results showed that based on the data exposure and data analysis that the authors described in the previous chapter, conclusions can be drawn according to the problems in this study, namely: 1) PAI Teachers' Contributions in Efforts to Form Discipline Characters and StudentResponsibilities at SMAN 4 Full Rivers. 2)Supporting Factors and Obstacles In Efforts to Form Disciplined Characters and Student Responsibilities at SMA N 4 Sungai Penuh.